Sappho Based on a Story by Alexandre Dumas - Hardy, Jack; Dumas, Alexandre (Grapevine Video, 2009)
Pola Negri's "Sappho" is a rare, largely unseen film that has been restored with its original tints and released on video for the first time ever, complete with a devastating orchestral score. The story is an ornate, contemporary costume drama about a notorious vamp whose long run of using men is brought to an abrupt halt when she meets the love of her life. However, the ghosts of her past haunt the new relationship, including the fact that she has previously driven her new beau's brother insane ... Sappho showcases Negri in many roles - a mother, a bride, a heartless socialite, a devoted lover - and each role she plays is completely and thoroughly believable. Her staredown of a former lover when he brandishes a gun jumps off of the screen; her silent scream at the film's end is so potent that it seems audible. The film itself was censored when it first reached American shores, and was only released in an altered version called "Mad Love"; this is the original, uncensored European version. [www.grapevinevideo.com]
Keywords: DVD-Video